Shadowplay : behind the lines & under fire : the inside story of Europe's last war - Marshall, Tim, 1959- (London : Elliott & Thompson Limited, 2019)
The last of the devastating series of conflicts resulting from the breakup of Yugoslavia in the early 1990s, the Kosovo War saw more than 13,500 fatalities, with reports of atrocities, amid controversial intervention and bombing by NATO. Twenty years have passed since the war's end on 11 June 1999, yet Kosovo's status remains uncertain and questions remain about the possibility of future conflict on European soil. Tim Marshall, then diplomatic editor at Sky News, was on the ground covering the war. This is his captivating account of how events unfolded, exploring the inside story of the way MI6 and the CIA helped the Serbian people to overthrow Slobodan Milosevic, the president of Yugoslavia. It is also a thrilling journalistic memoir, revealing key strategic insights that went on to shape the ideas behind the million-copy international and no.1 Sunday Times bestseller Prisoners of Geography. Drawing on personal experience, eyewitness accounts, and interviews with intelligence officials from five countries, this is the definitive account of one of the major events in recent geopolitical history, the repercussions of which continue to be felt today.
Keywords: Burgeroorlog Joegoslavië